Dahuang gancao dandelion decoction regulates intestinal flora and inhibits NF-κB/ARA signaling pathway to alleviate ulcerative colitis - Malajiang, Xieraili; Shen, Wan er; Aersilan, Alimu; Liu, Mengzi; Liang, Yuan; Wang, Shengyi; Abula, Saifuding; Wusiman, Adelijiang (Frontiers in Immunology, 2026)
ObjectiveThe aim of this study was to assess the therapeutic effects and underlying mechanisms of Dahuang Gancao Dandelion Decoction (DGD-D) on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in a mice model, with an emphasis on modulation of gut microbiota and intestinal metabolites, maintenance of intestinal barrier integrity, and inhibition of inflammatory signaling pathways.MethodsUltra-high-performance liquid chromatography with quadrupole electrospray ionization mass spectrometry (UHPLC-QE-MS) was used to examine the DGD-D, which was prepared from 40 g rhubarb, 10 g licorice, and 10 g dandelion. Potential routes and targets were found using network pharmacology. Six male C57BL/6 mice per group were randomized into control, DSS, DGD-D, and mesalazine (5-ASA) groups. UC was induced with 3% DSS for 7 days, with DGD-D administered prophylactically at 1950 mg/kg. Evaluated parameters included colon length, spleen index, and DAI, cytokine levels (ELISA, qRT-PCR), histological changes (H&E, PAS, AB-PAS), barrier proteins (IF, IHC, qRT-PCR), gut microbiota (16S rRNA sequencing), metabolites (LC-MS) and pathway validation.ResultsUHPLC-QE-MS identified 418 components in DGD-D, including flavonoids (25.12%) and phenolic acids (9.33%). Network pharmacology highlighted NF-κB signaling as a key pathway. In comparison to DSS, DGD-D dramatically decreased spleen index, restored colon length, and decreased DAI scores (P < 0.05). It increased anti-inflammatory IL-4 and IL-10 while downregulating pro-inflammatory cytokines (IL-1β, IL-6, IL-17, TNF-α, and IFN-γ) and MPO (P < 0.01). Histologically, DGD-D attenuated intestinal epithelial damage, increased goblet cells and glycoproteins, and enhanced ZO-1, Occludin, and MUC2 expression (P < 0.01). Microbiota analysis showed increased α-diversity, elevated Firmicutes/Bacteroidetes ratio, enriched beneficial Lachnospiraceae and Ruminococcaceae, and reduced Proteobacteria and Alcaligenaceae, Moraxellaceae and Xanthomonadaceae (P < 0.05). Metabolomics revealed downregulation of arachidonic acid (ARA) pathway mediators (ARA, LTA4, LTB4, LTD4; P < 0.001). DGD-D inhibited TLR4/MyD88/NF-κB p65/NLRP3/5-LOX expression (P < 0.01 or P < 0.001), suppressing NF-κB/ARA signaling.ConclusionDGD-D is a viable TCM-based treatment for UC since it improves DSS-induced UC by modifying gut microbiota and intestinal metabolites, reestablishing intestinal barrier function, and blocking the NF-κB/ARA pathway.